News Convergence Strategy For Human Resources Effectiveness: A Media Group Network Case Study - Rahmadani, Rina; Briandana, Rizki; Marta, Rustono Farady; Mohd Sofian, Muhammad Raqib (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2024)
Media consolidation and sustainability through convergence are proving to be effective strategies. Media Group Network (MGN) implemented a newsgathering convergence approach in 2021 based on human resources requirements. A project dubbed MGN Press brought together journalists from Media Indonesia, Metro TV, and Medcom.id. Multi-skilled individuals who can work across platforms are needed as journalists. The process is examined using the notion of media management strategy in broadcasting, which entails planning, organizing, directing, and controlling, to meet organizational objectives. In-depth interviews and observation are used as part of the case study methodology in this study. The study’s findings demonstrate that changing a journalist’s skill set is not an easy task. It is critical during the planning phase to assign the most qualified individual to oversee the convergence of newsgathering. Additionally necessary is the creation of organizations that represent the three platforms’ journalists. Media Group Network continues to direct and inspire despite a variety of constraints and challenges. The future deployment of newsgathering convergence can be improved using control and evaluation mechanisms. The news collecting convergence method may increase the effectiveness of human resources when it is put into practice.Keywords: Convergence, efficiency, human resources, newsgatheringABSTRAKKonsolidasi dan keberlanjutan media melalui konvergensi terbukti menjadi strategi yang efektif. Jaringan Grup Media (MGN) menerapkan pendekatan konvergensi pengumpulan berita pada tahun 2021 berdasarkan kebutuhan sumber daya manusia. MGN Press mempertemukan jurnalis dari Media Indonesia, Metro TV, dan Medcom.id. Individu multi-keterampilan yang dapat bekerja lintas platform dibutuhkan sebagai jurnalis. Proses tersebut ditelaah dengan menggunakan pengertian strategi manajemen media dalam penyiaran, yang mencakup perencanaan, pengorganisasian, pengarahan, dan pengendalian, untuk mencapai tujuan organisasi. Wawancara mendalam dan observasi digunakan sebagai bagian dari metodologi studi kasus dalam penelitian ini. Temuan penelitian menunjukkan bahwa mengubah keahlian jurnalis bukanlah tugas yang mudah. Sangat penting selama fase perencanaan untuk menugaskan individu yang paling memenuhi syarat untuk mengawasi konvergensi pengumpulan berita. Selain itu yang diperlukan adalah pembentukan organisasi yang mewakili jurnalis dari ketiga platform tersebut. Media Group Network terus mengarahkan dan menginspirasi meskipun dengan berbagai kendala dan tantangan. Penyebaran konvergensi pengumpulan berita di masa depan dapat ditingkatkan dengan penggunaan mekanisme kontrol dan evaluasi. Metode konvergensi pengumpulan berita dapat meningkatkan efektivitas sumber daya manusia ketika dipraktikkan.Kata Kunci: Konvergensi, efisiensi, sumber daya manusia, pengumpulan berita